Global Value Chain and Inward FDI in Southern Peripheral Euro Currency Area (ECA) Countries: The Portuguese Case - Dias, E.B. (World Investment Forum - 2014 -Academic Conference, 2014)
Focused on ‘greenfield’ and ‘brownfield’ inward FDI, our main research question is focused on which role will play Portugal, Spain, Italy and Greece in the Global Value Chain, taking into account the specialization of its economies. The value chain fragmentation and the liberalization of international trade – fewer constraints had an impact on FDI attraction, mainly on some local labor intensive industries (e.g. apparel and footwear, which were producing under private label contracts or arrangements), and a new challenge has been raised to the development of these economies. In order to understand which kind of local-specific resources are selected by international investors in these markets, we are developing a longitudinal case study approach, where variables are extracted in order to understand which kind of features/characteristics (tangible and intangible) are added in these territories. Our main conclusions, taking into account the Portuguese case, are: 1) skilled labor force at competitive costs; 2) logistics & location advantages in Trans-Atlantic flows and 3) near shore operations (not only in some services, but also in industries like apparel, footwear, machinery and tooling, among others). Regarding these main conclusions we are following three main research streams: 1) External Economies of Scale: Industrial Districts and Logistics; 2) Maritime Ports & Logistics: As Segments of the Global Value Chain; and, finally, 3) Global Value Chain Analysis (Value Fragmentation) and Coordination Tools.